Perubahan Tutupan Lahan Di Resort Pugung Tampak Taman Nasional Bukit Barisan Selatan (TNBBS) - Ricchardo P. Sinaga; Arief Darmawan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Land cover at Pugung Tampak Forest in Bukit Barisan Selatan National Park changing rapidly where forested area has been declined widely. Human activities such as land clearing, illegal logging, and agriculture is the ultimate cause of such deforestation in the region of Pugung Tampak Forest. Remote sensing and GIS techniques were used to monitor and evaluate any changes in land cover during the period of 1973-2011. This study aims to determine land cover change in 1973, 1997, 2002 and 2011 and to find out the land's cover change occured in Pugung Tampak Forest. This research was heldin January-September 2012. The data were collected from USGS glovis, direct observation in the field, interviewed with respondents and literature study. The data were analyzed by using Erdas 9.1 and Arcview 3.2 software. It was identified that most of the land cover in the Pugung Tampak Forest has been changed. During the period of 1973-2011 primary forest decreased about 8,737.87 ha (61.5%). The most of primary dry land forest was changed into bare land as much as 411.53 ha (23.9%), so the bare land in 2011 has increased from 82.6 ha to 4,998.43 ha (29.2%). Secondary dryforest land decreased by 389.89 ha (27.5%), dry land farming is increasing wide spread 4,642.58 ha (32.7%) and no data 430.62 ha (3.0%). Keywords: classification image, land covering change